STUDI AYAT-AYAT EKONOMI TENTANG AL-MILK SERTA KLASIFIKASI KEPEMILIKAN - Putri Nuraini (JURNAL ISLAMIKA, 2020)
Human life cannot be separated from economic activities. The existence of a source of Islamic law, namely the Quran, explains various problems in the economic field which contain universal values ​​about how the Islamic economy should be formulated. This research examines and explores the study of economic verses about al-milk and classification of ownership. This research methodology refers to the library approach (library research). This study focuses on the object of study in the form of written theoretical sources regarding al-milk and ownership classification. The results of this study, especially for the academic world, can be used as reference material (literature) which can add to the literature and science, especially in the clumps of Islamic economics and Islamic banking